Remdesivir in treating hospitalized patients with COVID-19: A renewed review of clinical trials - Wu, Zhenchao; Han, Zhifei; Liu, Beibei; Shen, Ning (Frontiers in Pharmacology, 2022)
Abstract: Since December 2019, COVID-19 has spread across the world almost through 2.5 years. As of June 16, 2022, the cumulative number of confirmed cases of COVID-19 worldwide has reached 542.62 million, and the death toll has risen to 6.33 million. With the increasing number of deaths, it is urgent to find effective treatment drugs. Remdesivir, an investigational broad-spectrum antiviral drug produced by Gilead has been shown to inhibit SARS-CoV-2, in vitro and in vivo. This review is aimed to analyze the feasibility of remdesivir in COVID-19 and put forward the shortcomings of present clinical studies. We systematically searched PubMed and Web of Science up until May 24, 2022, using several specific terms such as "remdesivir" or "GS-5734" and "COVID-19" or "SARS-CoV-2" and retrieved basic researches and clinical studies of remdesivir in COVID-19. In this review, we summarized and reviewed the mechanism of remdesivir in SARS-COV-2, clinical trials of using remdesivir in COVID-19, analyzed the efficacy and safety of remdesivir, and judged whether the drug was effective for the treatment of COVID-19. In different clinical trials, remdesivir showed a mixed result in the treatment of COVID-19. It seemed that remdesivir shortened the time to recovery and had an acceptable safety profile. However, more clinical trials are needed to test the efficacy and safety of remdesivir.